The effect of parenting style and demographic characteristic on simplified oral hygiene index in 6-12 year old children of Behbahan in 2018 - Roshanak i Montazeri Hedesh; Ghazaleh Baniebrahimi; Roza Haghgoo; Kosar Alinejad (Tehran University of Medical Sciences, 2021)
Background and Aims: Promoting children's oral health is the basis for increasing the level of community health and the goal of pediatric dentistry. By recognizing all the factors affecting the health and formation of the child's health habits, a fundamental step can be taken to promote oral health. The aim of this study was to evaluate the effect of parenting styles and demographic characteristic on OHI-S (Simplified Oral Health Index) in 2018. Materials and Methods: In this cross-sectional study, 244 children aged 6-12 years in Behbahan-Iran with their parents were studied. The demographic questionnaire (variables such as parents 'age, economic status, gender, occupation and parents' education were recorded) and Bumrind questionnaire were used. The oral health status of children was assessed to determine the simplified oral hygiene index. Then, the obtained data were analyzed using SPSS 25 software and regression and Pearson correlation test. Results:  The results showed that the children of parents who used the permissive method had higher score of simplified oral hygiene index (P<0.001) and simplified calculus index (P<0.001). However, in children of parents who used the authoritative parenting style, a decreased simplified oral hygiene index (P<0.001) and simplified debris Index (P<0.001) were observed. However, the method of authoritarian parenting style did not have a significant relationship with the simplified oral hygiene index (P=0.890), simplified calculus index (P=0.404), and simplified debris Index (P=0.721). Conclusion: Powerful authoritarin and authoritative parenting practices have a clear impact on the oral health status of children. Therefore, parenting paratices can be considered as one of the main factors affecting the oral health of children.